2014
DOI: 10.1111/ajsp.12091
|View full text |Cite
|
Sign up to set email alerts
|

Beware of friends: The cultural psychology of relational mobility and cautious intimacy

Abstract: Previous research has contrasted patterns of cautious or prevention-oriented relationality in various West African settings with patterns of growth or promotion-oriented relationality in many North American settings. The present research draws upon the concept of relational mobility to test the hypothesis that different patterns of relationality have their source in respective affordances for embedded interdependence or abstracted independence. Study 1 investigated the relationship between cautious intimacy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 43 publications
5
62
0
Order By: Relevance
“…The current research brings some implications in relational mobility. Evidence supporting the significant influence of relational mobility on interpersonal relationships has been accumulating (Li et al, 2015Lou & Li, 2017;Sato et al, 2014;Schug et al, 2009Schug et al, , 2010Yamada et al, 2015). However, enemyship has not been extensively examined from the perspective of relational mobility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current research brings some implications in relational mobility. Evidence supporting the significant influence of relational mobility on interpersonal relationships has been accumulating (Li et al, 2015Lou & Li, 2017;Sato et al, 2014;Schug et al, 2009Schug et al, , 2010Yamada et al, 2015). However, enemyship has not been extensively examined from the perspective of relational mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has consistently shown that the degree of (relational) mobility affects people's relationship construction as well as the form of their social networks (see Oishi, 2010; for a review). For instance, high mobility (vs. low mobility) would promote larger friendship networks (Lun, Roth, Oishi, & Kesebir, 2012), fewer cautions about friendship and less concern about existences of enemies (Li, Adams, Kurtis, & Hamamura, 2015). Mobility also extensively shapes people's strategies used in different types of social relationships (e.g., Li, Hamamura, & Adams, 2016;Lou & Li, 2017;Sato, Yuki, & Norasakkunkit, 2014).…”
Section: Relational Mobility and Enemyshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the expression of personal self is encouraged in these societies (Yamagishi, Hashimoto, & Schug, ). This, in turn, encourages the use of promotion‐oriented interpersonal strategies to maximize the chance for personal growth and positive interpersonal outcomes (Li, Adams, Kurtiş, & Hamamura, ). For instance, people in Western societies have a stronger tendency to expand their social network (Oishi et al., ) and use self‐disclosure as a tool for enhancing relationship intimacy (Schug, Yuki, & Maddux, ).…”
Section: Pspmentioning
confidence: 99%
“…In contrast, people in Asian societies (e.g., China, Japan, and Korea) experience a form of embedded interdependence (Adams, ). Interpersonal connection is in the form of dense overlapping networks rooted in a given social context, which in turn encourage the use of defensive (or prevention‐oriented) interpersonal strategies to maintain stable existing social relationships (Li et al., ). For instance, Asians are more likely to be motivated to understand their enemies (Li, Masuda, & Lee, ), save face (M. Chen, ; Wierzbicka, ), and suppress their negative emotions to preserve relationships (Matsumoto, ; Soto, Perez, Kim, Lee, & Minnick, ).…”
Section: Pspmentioning
confidence: 99%